What can the plasma proteome tell us about platelets (and vice versa)?. (31st December 2023) - Bruzek, Steven; Betensky, Marisol; Di Paola, Jorge; Diacovo, Thomas; Goldenberg, Neil; Ignjatovic, Vera
Abstract: Multi-omics approaches are being used increasingly to study physiological and pathophysiologic processes. Proteomics specifically focuses on the study of proteins as functional elements and key contributors to, and markers of the phenotype, as well as targets for diagnostic and therapeutic approaches. Depending on the condition, the plasma proteome can mirror the platelet proteome, and hence play an important role in elucidating both physiologic and pathologic processes. In fact, both plasma and platelet protein signatures have been shown to be important in the setting of thrombosis-prone disease states such as atherosclerosis and cancer. Plasma and platelet proteomes are increasingly being studied as a part of a single entity, as is the case with patient-centric sample collection approaches such as capillary blood. Future studies should cut across the plasma and platelet proteome silos, taking advantage of the vast knowledge available when they are considered as part of the same studies, rather than studied as distinct entities. Plain Language Summary: Platelets are key cellular elements of blood with plasma constituting the liquid component. Both platelets and proteins found in plasma rapidly work in unity to prevent/limit blood loss in response to blood vessel damage. Proteomics is the analysis of the entire protein complement of a cell, tissue, or organism under a specific, defined set of conditions. Of note, research to date has shown that platelet and plasma proteomes share many common proteins. In some disease scenarios, plasma proteomes can be used to identify platelet function or dysfunction, while in other scenarios, platelet-specific proteins are needed for physiological assessment. Thus, it may be beneficial to simultaneously study the plasma and platelet proteomes, thereby exploiting the considerable wealth of information provided under such circumstances.